Evaluation of the use of carbon nanotubes recovered from a biodegradation process in the production of new biodegradable polymer nanocomposites - Ana Paula Bernardo da Silva; Cássia Costa Girotto; Thaís Larissa Amaral Montanheiro; Marcelo Alexandre de Farias; Larissa Stieven Montagna; Dayane Batista Tada; Fernando Henrique Cristovan; Ana Paula Lemes (eXPRESS Polymer Letters)
The present study carried out the characterization of carbon nanotubes (CNT) recovered from the biodegradation process of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)/CNT nanocomposites and the use of this recovered CNT (CNT-rec) in the production of new PHBV nanocomposites. The results obtained by characterization of CNT-rec were very similar to the CNT. Therefore, it was possible to state that CNT properties were preserved during the biodegradation process; however, CNT-rec contained impurities such as proteins and residual PHBV. Regarding the performance as nanofillers, although both CNT and CNT-rec decreased the thermal stability of nanocomposites compared to neat PHBV, this effect was less intense in the CNT-rec nanocomposites. It is expected that both nanofillers acted as nucleating agents in the PHBV matrix crystallization process but with different effectiveness. There was no significant difference between the electrical conductivity comparing PHBV/CNT 2% and PHBV/CNT-rec 2% nanocomposites. Therefore, the recovery and use of CNT-rec is a feasible process.